Cerebral air embolism: neurologic manifestations, prognosis, and outcome - Červeňák, Vladimír; Všianský, Vít; Cviková, Martina; Brichta, Jaroslav; Vinklárek, Jan; Štefela, Jakub; Haršány, Michal; Hájek, Michal; Herzig, Roman; Kouřil, Dávid; Bárková, Veronika; Filip, Pavel; et al. (Frontiers in Neurology, 2024)
Background Cerebral air embolism (CAE) is an uncommon medical emergency with a potentially fatal course. We have retrospectively analyzed a set of patients treated with CAE at our comprehensive stroke center and a hyperbaric medicine center. An overview of the pathophysiology, causes, diagnosis, and treatment of CAE is provided. Results We retrospectively identified 11 patients with cerebral venous and arterial air emboli that highlight the diversity in etiologies, manifestations, and disease courses encountered clinically. Acute-onset stroke syndrome and a progressive impairment of consciousness were the two most common presentations in four patients each (36%). Two patients (18%) suffered from an acute-onset coma, and one (9%) was asymptomatic. Four patients (36%) were treated with hyperbaric oxygen therapy (HBTO), high-flow oxygen therapy without HBOT was started in two patients (18%), two patients (18%) were in critical care at the time of diagnosis and three (27%) received no additional treatment. CAE was fatal in five cases (46%), caused severe disability in two (18%), mild disability in three (27%), and a single patient had no lasting deficit (9%). Conclusion Cerebral air embolism is a dangerous condition that necessitates high clinical vigilance. Due to its diverse presentation, the diagnosis can be missed or delayed in critically ill patients and result in long-lasting or fatal neurological complications. Preventative measures and a proper diagnostic and treatment approach reduce CAE’s incidence and impact.